1984
DOI: 10.3109/10641968409046127
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Abnormalities Suggest a Dopaminergic Basis for High Blood Pressure in the Spontaneously Hypertensive Rat

Abstract: The spontaneously hypertensive rat (SHR) and the stroke-prone substrain (sp-SHR) have been reported to have several abnormalities in levels of peptides both in tissue and in plasma (beta-endorphin, prolactin, thyroid stimulating hormone and vasopressin) when compared to the Wistar Kyoto (WKY) normotensive control rat. As the secretion of these peptides is under dopaminergic control and the abnormalities consistently suggest under-activity of the dopaminergic control system in the brain, injections of dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The GHR, on the other hand, has been shown to have increased sympathetic tone (Clark & Phelan 1976) and increased peripheral vascular resistance (Simpson & Phelan 1984) compared with the normotensive (NT) rats. Previous work in this laboratory (Hutchinson & Mok 1984) showed that acute intracerebroventricular (i.c.v.) administration of dopamine to anaesthetized SHR and GHR produced significant falls in mean blood pressure (BP) in both strains.…”
Section: Introductionmentioning
confidence: 99%
“…The GHR, on the other hand, has been shown to have increased sympathetic tone (Clark & Phelan 1976) and increased peripheral vascular resistance (Simpson & Phelan 1984) compared with the normotensive (NT) rats. Previous work in this laboratory (Hutchinson & Mok 1984) showed that acute intracerebroventricular (i.c.v.) administration of dopamine to anaesthetized SHR and GHR produced significant falls in mean blood pressure (BP) in both strains.…”
Section: Introductionmentioning
confidence: 99%